N,N,N′,N′,N′′-Pentamethyl-N′′-[3-(trimethylazaniumyl)propyl]guanidinium bis(tetraphenylborate) - Tiritiris, Ioannis (International Union of Crystallography, 2013)
In the crystal structure of the title salt, C(12)H(30)N(4) (2+)·2C(24)H(20)B(−), the C—N bond lengths in the central CN(3) unit of the guanidinium ion are 1.3388 (17), 1.3390 (16) and 1.3540 (17) Å, indicating partial double-bond character in each. The central C atom is bonded to the three N atoms in a nearly ideal trigonal-planar geometry and the positive charge is delocalized in the CN(3) plane. The bonds between the N atoms and the terminal C-methyl groups of the guanidinium moiety, all have values close to a typical single bond [1.4630 (16)–1.4697 (17) Å]. C—H⋯π interactions are present between the guanidinium H atoms and the phenyl C atoms of one tetraphenylborate ion. The phenyl rings form a kind of aromatic pocket, in which the guanidinium ion is embedded.